Perancangan Strategi Pemasaran Digital Produk Olahan Kentang di Taman Teknologi Pertanian Cikajang - Ali Kamaludin; Hilmi Aulawi; Risa Aisyah (Institut Teknologi Garut, 2026)
This study aims to design a digital marketing strategy for processed potato products at the Cikajang Agricultural Technology Park (TTP) by utilizing the SOSTAC framework and the Analytical Hierarchy Process (AHP) method. The main problem faced is the suboptimal use of digital channels, resulting in sales being limited to nearby shops and direct purchases. Data were collected through interviews and questionnaires and then analyzed using Super Decisions software. The results show that the most influential criterion is the impact on sales (0.4412), while the priority strategies are TikTok Live and Interactive Content (0.3323). Other strategies such as Free Shipping, Giveaways and Local Events, and Instagram Marketing can be implemented as supporting strategies. Therefore, TTP Cikajang needs to focus on interactive social media strategies, particularly TikTok Live, to increase consumer engagement and expand the digital market.